Evaluating Yield Gap and Yield Improvement Potential in the Dairy Sector of Pakistan (The Pakistan Development Review, 2025)
A survey data of 600 dairy farms obtained from the largest dairy cluster in Pakistan’s Punjab was used to provide new evidence on the yield gap and yield improvement potential of dairy farms producing milk and meat. The yield gap was estimated by the frontier-based input distance function analysis. The results indicated that a large yield gap exists in the sample where an average dairy farm has a yield improvement potential of 55 percent. By closing the gap, an average dairy farm can increase yearly production of fat-corrected milk (FCM) by 120,036 kg and non-milking herd for meat by 25 heads. The evidence also shows that small farms (< 25 herd-size) are technically more efficient than those of medium (26 ? herd-size ? 50) and large farms (> 50 herd-size). The study finds clear evidence of an efficiency boost for keeping a higher share of non-milking to milking herd, a greater proportion of exotic cows to local breeds, and a higher farm-gate price of milk, which can all trigger efficiency gains. Policymakers hence have room to provide adequate intervention strategies that can help in enhancing efficiency.